THE IMPACT OF ECONOMIC INDICATORS ON FARMERS’ WELFARE IN TWO LEADING COFFEE-PRODUCING PROVINCES - Maria Michelle; Khusnul Khatimah (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
Indonesia's economy heavily depends on the agricultural sector, especially plantation crops, and the Farmers' Terms of Trade (NTP) are frequently used to gauge the welfare of farmers. South Sumatra and Lampung are the two provinces that produce the most coffee, yet their welfare dynamics do not always match their production dominance, suggesting a possible disconnect between output performance and farmer welfare. Using panel data from 2015 to 2023, this study attempts to investigate how sectoral GRDP, inflation, and coffee production affect Plantation Farmers' Terms of Trade (NTPB). A panel regression approach with high-frequency data is employed to better capture short-term welfare dynamics in leading coffee-producing regions, with the Common Effect Model identified as the most appropriate specification. The findings demonstrate that NTPB is significantly positively impacted by both GRDP and inflation. The beneficial impact of inflation should be read cautiously, too, since it probably represents price rises for agricultural commodities rather than general gains in buying power. Contrarily, coffee productivity has a negative and statistically negligible impact, suggesting that higher output does not always translate into improved farmer welfare. These findings reveal a structural discrepancy between production performance and welfare outcomes, suggesting that price dynamics and overall economic conditions have a greater impact on farmer welfare than productivity alone.